Copy letter from Roger Casement to Gertrude Bannister, expressing his admiration for Germany, having just returned from there, - Casement, Roger, 1864-1916 (1912)
Casement mentions a forthcoming book by Alice Stopford Green on Irish nationality that is intended as a rebuttal.